An approximation of the history of archaeological discoveries, as well as ethnographic and linguistic registers in 19th century Michoacán (Tzintzun, Revista de Estudios Históricos, 2016)
In this project, the irst archaeological discoveries registered in the landsof Michoacán during the 19th century are traced. It describes the eforts tofound a museum dedicated to the protection of the cultural heritage inheritedfrom the past, especially collections of archaeological objects, documents,ancient books, newspapers, photographs, ethnographic testimoniesof past generations of Michoacán people. Also, the project emphasizes theinterest from anthropological studies and concerning indigenous languages,especially Tarasco. It highlights the contributions made to this classof studies by the ecclesiastics José Guadalupe Romero, Francisco Plancarteand Navarrete and Sebastián Olivares, together with those of the doctorNicolás León and the Norwegian ethnologist Carl Lumholtz.
Keywords: archaeological discoveries; ethnographic registers; linguistic studies; 19th century